2017
DOI: 10.1021/acscatal.7b02954
|View full text |Cite
|
Sign up to set email alerts
|

Role of Conformational Dynamics in the Evolution of Retro-Aldolase Activity

Abstract: Enzymes exist as ensembles of conformations that are important for function. Tuning these populations of conformational states through mutation enables evolution toward additional activities. Here we computationally evaluate the population shifts induced by distal and active site mutations in a family of computationally designed and experimentally optimized retro-aldolases. The conformational landscape of these enzymes was significantly altered during evolution, as pre-existing catalytically active conformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
215
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 141 publications
(222 citation statements)
references
References 57 publications
7
215
0
Order By: Relevance
“…Interface 15: 20180330 the 23 mutations introduced during the directed evolution were located at positions that were distant from the active site, indicating that their impact is rather to influence the overall evolution of conformational dynamics of the enzyme. In particular, the conformational dynamics of flexible loops on the catalytic face of the TIM-barrel fold were affected by mutations, as shown by MD simulations [26]. Over the evolutionary trajectory of RA95, these loops were observed to become substantially more rigid, while the overall enzymes themselves gained increased thermostability [26,83].…”
Section: Retro-aldolasesmentioning
confidence: 96%
See 2 more Smart Citations
“…Interface 15: 20180330 the 23 mutations introduced during the directed evolution were located at positions that were distant from the active site, indicating that their impact is rather to influence the overall evolution of conformational dynamics of the enzyme. In particular, the conformational dynamics of flexible loops on the catalytic face of the TIM-barrel fold were affected by mutations, as shown by MD simulations [26]. Over the evolutionary trajectory of RA95, these loops were observed to become substantially more rigid, while the overall enzymes themselves gained increased thermostability [26,83].…”
Section: Retro-aldolasesmentioning
confidence: 96%
“…The importance of conformational dynamics for the evolution of enzyme activity was also showcased using MD simulations of a range of engineered retro-aldolases (RAs) [26]. Several RAs were designed de novo to break the C-C bond in unnatural substrate 4-hydroxy-4-(6-methoxy-2-naphthyl)-2-butanone (methodol) [79,80].…”
Section: Retro-aldolasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational methods have shown to be particularly useful in this regard . We have recently found that molecular dynamics (MD) simulations coupled to correlation‐based analysis can provide important insights on the alternative conformations that the enzyme can adopt in solution, but most importantly can predict which amino acid positions are key for favoring a desired population shift to enhance a promiscuous activity …”
Section: Figurementioning
confidence: 99%
“…Mutation of these residues might affect the position of the loop and hence substrate access to the active site. Any further increase in activity will probably require more mutations that are distal to the active site and could be predicted computationally …”
Section: Discussionmentioning
confidence: 99%